Associations between integrase strand-transfer inhibitors and cardiovascular disease in people living with HIV: a multicentre prospective study from the RESPOND cohort consortium. Issue 7 (July 2022) - Neesgaard, Bastian; Greenberg, Lauren; Miró, Jose M; Grabmeier-Pfistershammer, Katharina; Wandeler, Gilles; Smith, Colette; De Wit, Stéphane; Wit, Ferdinand; Pelchen-Matthews, Annegret; Mussini, Cristina; Castagna, Antonella; Pradier, Christian; et al.
Summary: Background: Although associations between older antiretroviral drug classes and cardiovascular disease in people living with HIV are well described, there is a paucity of data regarding a possible association with integrase strand-transfer inhibitors (INSTIs). We investigated whether exposure to INSTIs was associated with an increased incidence of cardiovascular disease. Methods: RESPOND is a prospective, multicentre, collaboration study between 17 pre-existing European and Australian cohorts and includes more than 32 000 adults living with HIV in clinical care after Jan 1, 2012. Individuals were eligible for inclusion in these analyses if they were older than 18 years, had CD4 cell counts and HIV viral load measurements in the 12 months before or within 3 months after baseline (latest of cohort enrolment or Jan 1, 2012), and had no exposure to INSTIs before baseline. These individuals were subsequently followed up to the earliest of the first cardiovascular disease event (ie, myocardial infarction, stroke, or invasive cardiovascular procedure), last follow-up, or Dec 31, 2019. We used multivariable negative binomial regression to assess associations between cardiovascular disease and INSTI exposure (0 months [no exposure] vs >0 to 6 months, >6 to 12 months, >12 to 24 months, >24 to 36 months, and >36 months), adjusted for cardiovascular risk factors. RESPOND is registered with ClinicalTrials.gov, NCT04090151, and is ongoing. Findings: 29 340 people living with HIV were included in these analyses, of whom 7478 (25·5%) were female, 21 818 (74·4%) were male, and 44 (<1%) were transgender, with a median age of 44·3 years (IQR 36·2–51·3) at baseline. As of Dec 31, 2019, 14 000 (47·7%) of 29 340 participants had been exposed to an INSTI. During a median follow-up of 6·16 years (IQR 3·87–7·52; 160 252 person-years), 748 (2·5%) individuals had a cardiovascular disease event (incidence rate of 4·67 events [95% CI 4·34–5·01] per 1000 person-years of follow-up). The crude cardiovascular disease incidence rate was 4·19 events (3·83–4·57) per 1000 person-years in those with no INSTI exposure, which increased to 8·46 events (6·58–10·71) per 1000 person-years in those with more than 0 months to 6 months of exposure, and gradually decreased with increasing length of exposure, until it decreased to similar levels of no exposure at more than 24 months of exposure (4·25 events [2·89–6·04] per 1000 person-years among those with >24 to 36 months of exposure). Compared with those with no INSTI exposure, the risk of cardiovascular disease was increased in the first 24 months of INSTI exposure and thereafter decreased to levels similar to those never exposed (>0 to 6 months of exposure: adjusted incidence rate ratio of 1·85 [1·44–2·39]; >6 to 12 months of exposure: 1·19 [0·84–1·68]; >12 to 24 months of exposure: 1·46 [1·13–1·88]; >24 to 36 months of exposure: 0·89 [0·62–1·29]; and >36 months of exposure: 0·96 [0·69–1·33]; p<0·0001). Interpretation: Although the potential for unmeasured confounding and channelling bias cannot fully be excluded, INSTIs initiation was associated with an early onset, excess incidence of cardiovascular disease in the first 2 years of exposure, after accounting for known cardiovascular disease risk factors. These early findings call for analyses in other large studies, and the potential underlying mechanisms explored further. Funding: The CHU St Pierre Brussels HIV Cohort, The Austrian HIV Cohort Study, The Australian HIV Observational Database, The AIDS Therapy Evaluation in the Netherlands National Observational HIV cohort, The EuroSIDA cohort, The Frankfurt HIV Cohort Study, The Georgian National AIDS Health Information System, The Nice HIV Cohort, The ICONA Foundation, The Modena HIV Cohort, The PISCIS Cohort Study, The Swiss HIV Cohort Study, The Swedish InfCare HIV Cohort, The Royal Free HIV Cohort Study, The San Raffaele Scientific Institute, The University Hospital Bonn HIV Cohort and The University of Cologne HIV Cohorts, ViiV Healthcare, and Gilead Sciences.